Pengaruh Equivalent Rate dan Tingkat Keuntungan Terhadap Dana Pihak Ketiga (DPK) Perbankan Syariah di Indonesia - Vera Susanti Vera Susanti (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2015)
The aims of this research are to explain and analyze the effect ofequivalent rate and rate of return on the third party accounts of IslamicCommercial Banking (BUS) and Syariah Business Unit (UUS) in Indonesia. Theresearch was conducted with quantitative descriptive methods by usingsecondary data. The data obtained from Islamic Banking statistic report ofBank Indonesia 2009‐2013. By using multiple linear regressions this researchfinds out that equivalent rate and rate of return significantly influence the thirdparty accounts of Islamic Commercial Banking and Syariah Business Unit inIndonesia 2009‐2013. It was showen by partially t test that indicate t valued(4,018) > t table (2,004) of equivalent rate variable and t valued (6,156) > ttable of return rate variable. Simultaneously F test also indicate that F valued(50,109) > F Table 2,790. This research suggests that Islamic CommercialBanking and his Syariah Business Unit should increase the volume of equivalentrate and share of return rate saving accounts in order to increase third partyaccounts that significantly determine the performance of Islamic banking in thefuture.Key Words: Equivalent Rate, Rate of Return, Third Party Accounts and Islamic Banking